2020
DOI: 10.1097/iop.0000000000001514
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Smoking on Mitochondrial Biogenesis in Patients With Graves Ophthalmopathy

Abstract: Purpose: To evaluate the effects of cigarette smoking on oxidative stress (OS) and mitochondrial biogenesis related parameters in patients Graves Ophthalmopathy (GO). Methods: Patients with moderate-to-severe GO according to the European Group on Graves Orbitopathy (EUGOGO) criteria were prospectively enrolled in this study. Age- and sex-matched healthy volunteers who applied to outpatient clinic due to refractive problems consisted the control group. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…To date, only one study has been published to assess the PON-1 activity in euthyroid patients with GD and TAO. It demonstrated significantly lower PON-1 activity in subjects with TAO as compared to controls, with euthyroid state not affecting PON-1 activity levels [44]. To the best of our knowledge, ours is the first study to assess the serum PON-1 activity in patients with GD and TAO depending on their thyroid hormone status.…”
Section: Original Papermentioning
confidence: 61%
“…To date, only one study has been published to assess the PON-1 activity in euthyroid patients with GD and TAO. It demonstrated significantly lower PON-1 activity in subjects with TAO as compared to controls, with euthyroid state not affecting PON-1 activity levels [44]. To the best of our knowledge, ours is the first study to assess the serum PON-1 activity in patients with GD and TAO depending on their thyroid hormone status.…”
Section: Original Papermentioning
confidence: 61%
“…Czarnywojtek et al suggested the concentration of urine cotinine as a quantitative and qualitative indicator of tobacco smoking, which was found to be associated with the exacerbation of ophthalmopathy in patients with GD [ 45 ]. Yoksel et al reported that the total oxidant status and oxidative stress index values were higher in patients with GO who smoked compared with either patients with GO who did not smoke or healthy controls [ 46 ]. Tsai et al also found that smokers had higher urinary levels of 8-hydroxy-2′-deoxyquanosine (8-OHdG) than never smokers in patients with GO [ 18 ].…”
Section: Cigarette Smoking and Graves’ Ophthalmopathymentioning
confidence: 99%
“…Moreover, it has been deeply studied that the toxicants contained in cigarette smoke can cause a relevant genetic damage by increasing the oxidative stress and an imbalance between pro-inflammatory and anti-inflammatory immune response [72][73][74]. As a result, in smokers autoimmune diseases like rheumatoid arthritis, systemic lupus erythematosus and Graves' disease are more frequent and severe [75][76][77][78][79][80][81][82][83].…”
Section: Environmental Factorsmentioning
confidence: 99%